TRENDS AND DEVELOPMENT OF THE ONSHORE WIND ENERGY INDUSTRY IN TAMAULIPAS, MEXICO - REQUENA HERNANDEZ, Lidia Elena; SOLIS MARTINEZ, Hugo Alberto; MUÑOZ LEDEZMA, Lilian; TOLEDO GONZALEZ, Noé; GONZALEZ MORENO, Humberto Raymundo (Modern Management Review, 2023)
The expansion of renewable energy has not changed, nor the fundamentals which they are ruled with, and their share in world electricity generation reached almost 27% in 2019; currently, solar PV and onshore wind are already the cheapest way to incorporate new electricity generating plants in most countries. Disruptions to the renewable energy supply chain, caused by the COVID-19 crisis, slowed the progress of any project globally during the first six months of 2020, however, plants construction and manufacturing activity intensified again starting in the second half of the year and logistical challenges were mostly resolved with the easing of cross-border restrictions. The purpose of this article is to carry out an analysis of the development of the energy market of the second renewable source with the highest installed capacity in Mexico and the first with highest installed capacity in Tamaulipas: onshore wind and its trends that predominate globally.